Brand equity and firm performance : evidence from trading and service sector in Malaysia - Lim, Chin Chien (Universiti Malaysia Sarawak, (UNIMAS), 2010)
The purpose of this study is to investigate interrelationships between brand equity and firm performance in Malaysia. The study used a sample of 100 firms in trading and service sector listed on the Bursa Malaysia in 2008. The methodology applied in this study is Multiple Ordinary Least Squares (OLS) regression. The result indicated that brand equity could affect the firm performance and thus, influence the stock price of the firm. The brand equity of the firm could further enhance firm performance. Therefore, this result confirms that there is a positive relationship between brand equity and firm performance.